Peran Dinas Perhubungan Kota Surabaya dalam Pengelolaan Parkir Umum Pinggir Jalan yang Efektif dan Efisien - Abel Dwi Purnomo (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
The rapid development of digital technology has significantly transformed Islamic microfinance, particularly through the adoption of artificial intelligence in micro digital financial services. Artificial intelligence offers strong potential to enhance efficiency, transparency, and financial inclusion for underserved communities, especially within Islamic microfinance institutions such as Baitul Maal wat Tamwil. However, the integration of artificial intelligence also raises legal and ethical challenges related to accountability, data protection, Sharia compliance, and consumer protection. This study examines legal protection and regulatory frameworks governing the use of artificial intelligence in Islamic micro digital finance from the perspective of Islamic ethics and national law. Employing a normative juridical approach supported by literature analysis, the study emphasizes the need to align technological innovation with Sharia principles, ethical values, and positive legal norms. The findings show that artificial intelligence can promote transparency and financial inclusion when supported by clear legal regulation, effective Sharia supervision, and ethical governance. Overall, synergy between law, technology, and Islamic ethics is crucial to ensure sustainable, fair, and inclusive Islamic microfinance development.